QUALITY ASSURANCE IN EDUCATION, RESEARCH AND ACCOUNTABILITY - Boland, Tom (My University, 2013)
“There is a broad consensus globally of the value of education to social and economic development. Higher education in particular plays a crucial role in creating culturally vibrant and democratic societies. Higher education and research, and the outcomes they produce in terms of well-educated graduates, a capacity for innovation and new knowledge, play crucial roles in the economic development of all our societies. So we can agree that well performing higher education institutions, accessible to all who can benefit from higher education and graduating high quality graduates is a worthwhile objective for all of us.”--
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; economic development; higher education; education